Designing A Future Workforce Skills Framework: A Gap Analysis Of Future Workforce Skills Between Academicians And Manufacturing Industry Players - Rodzalan, Shazaitul Azreen; Mohd Noor, Noor Nazihah; Abdullah, Nor Hazana; Mohamed Saat, Maisarah (2024)
This study underscores the critical need to prepare the youth for the challenges of Industry 4.0, requiring a paradigm shift in skills due to rapid technological advancements. Notably, in Malaysia, employers’ express concerns about a skills mismatch, contributing to elevated unemployment rates. Centered on the manufacturing sector, the research employs a gap analysis to discern and address the skills disparities between academic institutions and industry stakeholders, encompassing both essential soft and hard skills crucial for the future workforce. The resulting framework aims to precisely outline the skills required for the evolving job landscape, crucial for sustaining Malaysia’s economic dependence on manufacturing. The findings underscore substantial gaps in both soft and hard skills between academicians and industry, emphasizing the urgency for targeted skill development initiatives. The study’s insights offer valuable guidance for industries, educational institutions, policymakers, and the Malaysian youth enabling them to rectify deficiencies and cultivate a workforce that is well-prepared for the future, aligning with Malaysia’s economic aspirations of becoming a robust, high-income nation.